Effects of seasonal grazing on plant and soil microbial diversity of typical temperate grassland - Ma, Chun-Hui; Hao, Xing-Hai; He, Feng-Cai; Baoyin, Tao-Getao; Yang, Jue-Jie; Dong, Shi-Kui (Frontiers in Plant Science, 2022)
Biodiversity is the decisive factor of grassland ecological function and process. As the most important human use of grassland, grazing inevitably affects the grassland biodiversity. However, comprehensive studies of seasonal grazing on plant and soil bacterial, archaeal and fungal diversity of typical temperate grassland are still lacking. We examined the impact of seasonal grazing, including no-grazing (NG), continuous grazing (CG), grazing in May and July (G57), grazing in June and August (G68), and grazing in July and September (G79) on grassland plant and soil microbial diversity based on a long-term field grazing experiment. The results showed that the aboveground plant biomass (AGB) of the seasonal grazing plots was significantly higher than that of the CG plots. Compared with NG, CG increased significantly the Margalef richness index of plant community, while did not significantly change the Shannon, Simpson and Pielou evenness of plant community. Grazing changed the composition and biomass of dominant vegetation. Long-term grazing decreased the proportion of Leymus chinensis (Trin.) Tzvel. and increased the proportion of Cleistogenes squarrosa (Trin.) Keng. There was no significant change in the Shannoneven, Shannon and Coverage indices of soil bacteria, archaea and fungi between NG and the grazing plots. But the Chao index of soil fungi in G57, G68 and G79 and archaea in G57, G79 was significantly higher than that in CG. The results of correlation analysis showed that the plant diversity in the CG plots was significantly negatively correlated with the soil bacterial diversity. The plant richness in the G57 and G68 plots was significantly positively correlated with the soil archaea richness. Our study showed that seasonal grazing was a sustainable grazing management strategy for maintaining typical grassland plant and soil microbial diversity in northern of China.